Growth performance of broiler chickens fed fossil shell growth promoter (2013)
A study was carried out to determine the influence of fossil shell (diatomaceous earth) supplemented diets on the performance and bone composition of broiler chickens. A total of 120 day old broiler chicks were used for the experiment and randomly allotted to 5 treatments (Tl—0.9%, T2—1.2%, T3—1.5%, T4—1.8% and T5—0% inclusion levels respectively). Fossil shell inclusion had no significant influence on feed intake and feed conversion ratio, but had significant impact on weight gain. At the finisher phase no significant differences (p > 0.05) were observed for weight gain, feed intake and feed: gain ratio. Bone analysis showed that calcium content was not affected but fossil shell had significant influence on phosphorus content of the analyzed bones.